(untitled) (Journal of Hama University, 2024)
earch aimed to identify the role of the kindergarten curriculum in promoting healthy nutritional awareness among the child from the point of view of kindergarten teachers in Lattakia city, and to know the differences in the views of the sample members of kindergarten teachers about the role of the kindergarten curriculum in promoting healthy nutritional awareness in the child according to the following variables: (scientific and educational qualification, and the number of years of experience), and used the descriptive approach. The sample included (116) kindergarten teachers. To achieve the objective of the research, a questionnaire was designedconsisting of (28) phrases, about the role of the kindergarten curriculum in promoting healthy nutritional awareness among children. The results of the research showed that the role of the kindergarten curriculum in promoting healthy nutritional awareness among the child came to a medium degree according to the estimate of kindergarten teachers, and the results showed a statistically significant difference in the views of kindergarten teachers on the role of the kindergarten curriculum in promoting healthy nutritional awareness in the child according to the variable of scientific and educational qualification in favor of teachers whohold a license in education, and there were no statistically significant differences in the views of kindergarten teachers on the role of the kindergarten curriculum in promoting healthy nutritional awareness in the child according to the variable of the number of years of experience. The research made many proposals, the most important of which are: including kindergarten curricula, supporting them in an adequate way to enhance healthy nutritional awareness among children, and conducting research on the views of kindergarten principals on the role of the kindergarten curriculum in promoting healthy nutritional awareness in the child.